2012
DOI: 10.1177/0266242612458517
|View full text |Cite
|
Sign up to set email alerts
|

Extending open innovation throughout the value chain by small and medium-sized manufacturers

Abstract: This study assesses the adoption of open innovation practices during different value chain activities and measures its effect on product and process innovation. Based on a quantitative survey of 293 US small and medium-sized manufacturing companies the empirical research results suggest a broad use of open innovation practices with customers and suppliers throughout the firm's value chain. Strong interrelationships between open innovation practices along with the varied impact of open innovation practices on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 50 publications
6
83
0
3
Order By: Relevance
“…However, Lecocq and Demil (2006) found that open systems strategy in an industry creates an entry induction phenomenon and new entrants adopt the open systems more readily than the incumbents. SMEs need to focus significantly on the selection of practices and partners (Theyel 2013). SMEs develop searching strategies for various activities such as new knowledge, innovative ideas, partners, and potential market.…”
Section: Searching Strategymentioning
confidence: 99%
“…However, Lecocq and Demil (2006) found that open systems strategy in an industry creates an entry induction phenomenon and new entrants adopt the open systems more readily than the incumbents. SMEs need to focus significantly on the selection of practices and partners (Theyel 2013). SMEs develop searching strategies for various activities such as new knowledge, innovative ideas, partners, and potential market.…”
Section: Searching Strategymentioning
confidence: 99%
“…As a scientific contribution, we continue the discussion on the management of co-innovation within value networks (Gassman et al, 2010;Ritala et al, 2013Ritala and Huizingh, 2014;Ritala, P. and Tidström, 2014;Wynarczyk, et al, 2013;Theyel, 2013). By studying the Hub's practiced strategy also by interviewing the SMEs and VCs on their co-innovation management views, we could bring the most controversial issues of innovation networks to light.…”
Section: Commitment Vs Independencymentioning
confidence: 85%
“…Smith et al (2014) concluded that partners should identify and learn from the collaboration barriers in the ecosystem. Especially the smaller participants of a supply chain should focus on selection of practices and partners to achieve successful collaboration in innovation (Theyel, 2013). Even though innovation is praised in scientific literature, many aspects of innovation management practices especially related to change towards and challenges within innovation embracing value networks have not yet been studied.…”
Section: Management Of Innovative Supply Networkmentioning
confidence: 99%
“…In the context of digital business operations, empirical studies (Jansen et al 2013;Theyel 2013) suggest that SMEs tend to integrate strategic business activities effectively with their trading partners in the value chain in order to achieve high level of coordination efficiency. SMEs employing strategic integration with their business partners are likely to increase coordination efficiency of production through close integration of decisions and operations (Voss & Voss 2013).…”
Section: H5: It Integration Is Related Positively To Coordinationmentioning
confidence: 99%
“…Recent research (Jansen et al 2013;Wynn 2008) demonstrates that the inter-firm collaboration and coordination helps SMEs to increase the intensity of, and enrich the quality of, its interactions with partners and suppliers, thus enhancing business relationship development. SMEs sharing important product planning and inventory information with value chain members on a regular and realtime basis are more likely to develop productive relationships than those who do not (Raymond & Bergeron 2008;Theyel 2013). In addition, an important precursor to effective and efficient inter-firm processes is the commitment of resources among value chain members to ensure that their business processes and systems are mutually compatible (Bharadwaj & Soni 2007).…”
Section: H5: It Integration Is Related Positively To Coordinationmentioning
confidence: 99%